Multiple choice: How public school leaders in New Orleans's saturated market view private school competitors - Huriya Jabbar; Dongmei Li (Arizona State University, 2016)
School choice policies, such as charter schools and vouchers, are in part designed to induce competition between schools. While several studies have examined the impact of private school competition on public schools, few studies have explored school leaders' perceptions of private school competitors. This study examines the extent to which public school leaders in New Orleans, which already has a robust public school choice system, perceived competition with private schools, and the characteristics that predicted competition between the two types of schools. We find that while over half of principals reported competing with private schools for students, there was a wide range of the number and percentage of possible competitors reported. Furthermore, the results suggest that school voucher policies did not play a major role in influencing why schools competed with private schools. In addition, public school leaders who did lose students to private schools through the voucher program reported that they often recouped those losses, when parents returned to public schools unsatisfied or facing additional unexpected costs.